The role of BATF2 during of experimental murine Schistosomiasis - Mpotje, Thabo Rantanta Victor (Department of Pathology, 2018)
Schistosomiasis is one of the most debilitating tropical diseases with the potential to cause morbidity and mortality in infected populations unless well controlled. Current control measures are limited to treatment with praziquantel. A rather alarming situation given i) the inability of the drug to directly target the pathogenic eggs, ii) the emergence of praziquantel-resistant schistosomes, iii) the persistence of tissue fibro-proliferative destruction caused by the trapped parasite eggs, even after treatment. Intestinal and liver immunopathology are pathognomonic of schistosomiasis and generally result from the host inadequate Th2 and or Th17 responses to the egg-derived antigens. Failure to control these immune responses causes the most of the detriment to the infected host, highlighting the need for a better understanding of the regulatory mechanisms which might help prevent excessive immune responsiveness and the ensuing immunopathology. A Basic leucine zipper transcription factor ATF-like 2 (BATF2) which belongs to a family of transcription factors critical in the control of inflammatory responses has gained enormous momentum recently as a potential target to immune deregulation during cancer and infectious diseases. We reasoned that an eventual BATF2 influence on the host immune response during schistosomiasis might unveil its anti-disease potency and greatly facilitate the quest for a novel control strategy against the immunopathology during schistosomiasis. Addressing this in our present study, BATF2-deficient mice were used and characterized for immunological and physiological parameters during steady state and Schistosomiasis. Although the liver showed a reduced pro-fibrotic response, there was a notable increase of several pro-fibrotic cytokines (TNF-α, IFN-ƴ, TGF-β and IL-13) Which further translated into an elevated level of granulomatous inflammation and fibrosis in the gut of S. mansoni infected BATF-2-deficient mice when compared to the liver tissues of BATF2-deficient mice and both livers and intestines of infected littermate controls indicating that BATF2 appears to have a tissue-specific role on the regulation of fibrogranulomatous inflammation during schistosomiasis. Therefore, BATF2 has a critical, and hitherto unappreciated, role in mediating the regulation of gut fibrogranulomatous response so as to promote host survival during schistosomiasis.